2017
DOI: 10.1080/00071668.2017.1401215
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic assessment of concussive non-penetrative captive bolt stunning of turkeys

Abstract: 1. The aim of this study was to evaluate the electroencephalographic (EEG) and behavioural responses of turkeys stunned with three different concussive non-penetrative captive-bolt guns prior to slaughter. 2. A total of 31 slaughter weight ex-breeding female turkeys (29 weeks of age; mean body weight 13.32 ± SD 0.65 kg) were stunned with the Cash Poultry Killer (CPK) (n = 10), Turkey Euthanasia Device (TED) (n = 10) and Zephyr EXL (n = 11). 3. Mean peak kinetic energy was highest for the CPK compared to the TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 27 publications
1
34
1
Order By: Relevance
“…cervical dislocation) to ensure death. However, scientific evidence has demonstrated that if captive bolt is properly applied in poultry, stunning is already enough to kill the animal (Raj and O'Callaghan, ; Erasmus et al., ,b; Gibson et al., ). It has been suggested that the appropriate specifications for captive bolt stunning of broilers are a minimum of 6 mm bolt diameter driven at an air pressure of 827 kPa to a penetration depth of 10 mm (Raj and O'Callaghan, ).…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…cervical dislocation) to ensure death. However, scientific evidence has demonstrated that if captive bolt is properly applied in poultry, stunning is already enough to kill the animal (Raj and O'Callaghan, ; Erasmus et al., ,b; Gibson et al., ). It has been suggested that the appropriate specifications for captive bolt stunning of broilers are a minimum of 6 mm bolt diameter driven at an air pressure of 827 kPa to a penetration depth of 10 mm (Raj and O'Callaghan, ).…”
Section: Assessmentmentioning
confidence: 99%
“…It has been suggested that the appropriate specifications for captive bolt stunning of broilers are a minimum of 6 mm bolt diameter driven at an air pressure of 827 kPa to a penetration depth of 10 mm (Raj and O'Callaghan, 2001). Other authors concluded that the use of captive bolts in turkeys, ducks and geese is effective in inducing death, when properly applied involving similar parameters as in broilers (Erasmus et al, 2010a,b;Sparrey et al, 2014;Gibson et al, 2018). In any case, death should be confirmed after shooting with the captive bolt gun to eliminate the risk of birds surviving due to human error or equipment failure, and, if animals are not dead, a back-up killing method should be applied.…”
Section: Process Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shooting of two broilers with a 6‐mm bolt at 620 kPa resulted in effective stunning and a very rapid recovery of consciousness in one bird and death in the other. Similarly, Gibson et al. (2018) evaluated three different commercially available non‐penetrating captive bolt guns in turkeys and reported that accurate shooting and enough cartridge power are critical to achieving effective stunning.…”
Section: Assessmentmentioning
confidence: 99%
“…These are generally powered by compressed air, gun powder, or propane. With sufficient airline pressures or powerloads and when placed in the correct position (top of the head on the midline between the eyes and ears), they can be effective in inducing unconsciousness in turkeys and chickens without recovery [2][3][4][5], while variation from the ideal shooting position and inconsistencies in powerloads was reported to result in incomplete concussion in slaughter weight turkeys following stunning with three different NPCB guns, using electroencephalographic (EEG) and behavioural indices to evaluate unconsciousness [4]. Erasmus et al [6] and Woolcott et al [5] examined pathology only or pathology and behaviour respectively after NPCB stunning in turkeys and concluded that pneumatic NPCB stunning was effective in producing profound damage to the brain, which was hypothesised to be responsible for death.…”
Section: Introductionmentioning
confidence: 99%